Anterior Urethral Rupture with Extravasation of Urine to Penis and Scrotum: A case report - Setyo Sutanto (Syntax Idea)
Urethral Trauma is a discontinuity of urethra which caused by external stress (pelvic fracture or straddle injury) or internal stress (catheter placement, urological procedures). There are several suitable techniques, including immediate exploration or urine diversion. The treatment used depend on the cause of the rupture, rupture length, as well as anatomical position of the rupture. A 46-year-old male suddenly presented with swollen penile and testicle after 1 day of hospitalization. One day before, patient suffers in high-speed motorcycle accident and sustains blunt trauma to the perineal area, hitting the handle bar of the motorcycle and brought to the emergency department. There was a palpable bladder distension during physical exam, with penis and scrotum enlargement. Laboratory findings show elevated WBC and elevated creatinine level. Urinalization test was within normal limit. Partial laceration found during urethroscopy approximately <1cm in size. Scrotal drainage and exploration are conducted due to scrotum being swollen progressively. There is uncertainty regarding these symptoms to be interpreted as a urethral injury because some of the classical symptoms are missing, although patient showed with palpable bladder distension. Due to the swollen penis and scrotum which are enlarged progressively, urethroscopy and scrotal exploration was performed. Small laceration on the bulbar area of the urethra is found, indicating anterior urethral rupture, the laceration is treated conservatively with the placement of transurethral catheter. Scrotal exploration then performed which pus and extravasation of urine is found within the scrotum. The precision on determining anterior urethral rupture as a diagnosis decides the management, prognosis and complication rate of anterior urethral rupture. Although, the initial urethral trauma management remains disputed, a bulbous urethral rupture with a complication of extravasation of urine into the penis and scrotum can be treated effectively with urine diversion and scrotal exploration Urethral Rupture